Pengaruh Mata Kuliah Kewirausahaan dan Lingkungan Keluarga Terhadap Minat Berwirausaha pada Mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung Tahun Akademik 2024/2025 - Vellani, Dignia Ayu; Gufron, Moh. (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Entrepreneurial interest is the desire, interest, and willingness to work hard or strong will to be independent or try to meet their needs without being afraid of the risks that will occur, and the willingness to learn from failure. The purpose of this study was to determine the effect of entrepreneurship courses and family environment on the entrepreneurial interest of students of the Economics Education Study Program, Bhinneka PGRI University, Tulungagung, Academic Year 2024/2025. The data collection method was with a questionnaire to obtain data on entrepreneurship courses (variable X1), family environment (X2) and entrepreneurial interest (variable Y). The instrument used was an existing statement. To determine the relationship between the three variables X1, X2 and Y, the rough product moment correlation formula was used. From the results of the data analysis, the F_count value> F_table was obtained, namely 225.449> 3.952 and the significance was 0.000 <0.05. The results of this study are that "There is an influence of entrepreneurship courses and family environment on the entrepreneurial interest of students of the Economic Education Study Program, Bhinneka PGRI University, Tulungagung, Academic Year 2024/2025".